Turnover Intention among Generation Z Employees: The Role of Workload, Social Support, and the Mediating Effect of Job Stress - Jeffry Latumahina; Nurzalinar Joesah; Agtovia Frimayasa (Sean Institute, 2026)
This study investigates the relationships among workload, social support, job stress, and turnover intention among Generation Z employees, with job stress examined as a mediating variable. Using a quantitative causal design, data were collected from 100 Generation Z employees and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results indicate that workload has a positive and significant effect on job stress, while job stress exerts a strong positive influence on turnover intention. Social support significantly affects job stress but shows a negligible direct effect on turnover intention. Mediation analysis confirms that job stress significantly mediates the relationships between workload and turnover intention, as well as between social support and turnover intention, with partial mediation observed for workload and dominant mediation for social support. These findings highlight job stress as a key psychological mechanism linking work conditions to turnover intention. The study contributes to the literature by integrating job demands and social resources in explaining turnover intention among Generation Z employees and provides practical implications for employee retention strategies.